PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP BANGUN RUANG SISI DATAR MELALUI PMRI DENGAN APLIKASI LEARNING MANAGEMENT SYSTEM (LMS) - Erna Sari Agusta (LPMP Provinsi DKI Jakarta, 2023)
The ability to understand concepts is one of the skills that must be mastered by students in mathematics. However, the ability to understand the concepts of MTsN 28 Jakarta students is still relatively low. The existence of the implementation of PTM Limited (PTMP) resulted in learning only being a process of transferring formulas and uploading assignments. Therefore, we need an innovation that can make learning more meaningful. PMRI can be a solution so that students are involved in learning. To overcome time constraints, PMRI can be implemented with the help of the Learning Management System (LMS) application. The purpose of this study was to find out the application of the PMRI approach assisted by the LMS application in improving the ability to understand the concept of Building Flat Sided Spaces in class VIII-2 students of MTsN 28 Jakarta. This study uses a qualitative approach with the type of Classroom Action Research (PTK) which is carried out in three cycles. The research subjects observed in the study were 6 students from the upper, middle and lower groups. Data analysis refers to the achievement of indicators of understanding the concept as seen from the results of the research subject's test answers through three stages, namely: data reduction, data presentation, and drawing conclusions. The results showed that the average test score increased from 69.97 in cycle I, 73.06 in cycle II, and 78.18 in cycle III. Students who reached KKM also experienced an increase, in the final test of cycle I there were 7 people (23.33%), in cycle II it increased to 16 people (50%), and in cycle III again it increased to 23 people (76.67%) . The increase in test scores is also supported by the addition of concept understanding indicator scores. Thus, it can be said that the PMRI approach assisted by the LMS application can improve students' understanding of mathematical concepts.